Intraepithelial lymphocytes in the pig intestine: T cell and innate lymphoid cell contributions to intestinal barrier immunity - Wiarda, Jayne E.; Loving, Crystal L. (Frontiers in Immunology, 2022)
Intraepithelial lymphocytes (IELs) include T cells and innate lymphoid cells that are important mediators of intestinal immunity and barrier defense, yet most knowledge of IELs is derived from the study of humans and rodent models. Pigs are an important global food source and promising biomedical model, yet relatively little is known about IELs in the porcine intestine, especially during formative ages of intestinal development. Due to the biological significance of IELs, global importance of pig health, and potential of early life events to influence IELs, we collate current knowledge of porcine IEL functional and phenotypic maturation in the context of the developing intestinal tract and outline areas where further research is needed. Based on available findings, we formulate probable implications of IELs on intestinal and overall health outcomes and highlight key findings in relation to human IELs to emphasize potential applicability of pigs as a biomedical model for intestinal IEL research. Review of current literature suggests the study of porcine intestinal IELs as an exciting research frontier with dual application for betterment of animal and human health.